Xenotransplantation Clinical Trials and the Need for Community Engagement. Issue 5 (13th October 2022) - Gusmano, Michael K.
Abstract: There are several ethical concerns facing first‐in‐human clinical trials involving xenotransplantation. Who should participate in these trials? If we limit trial participation to those who have exhausted other treatment options, how can we avoid therapeutic misconception? How should we balance the desire for long‐term monitoring of trial participants against the well‐established principle that research participants have the right to withdraw from research? Finally, how should we balance concerns about equitable access to these trials with deep mistrust of the scientific community? In particular, should xenotransplant clinical trials attempt to address well‐known inequities in clinical trial participation by race and ethnicity? In this commentary, I argue that clinical investigators and regulators have an obligation to engage with underrepresented communities to develop answers to these questions .